Le Proche-Orient dans le système mondial - Hentsch, Thierry (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The Middle East is generally perceived in the West, often in simplistic terms, as an area which is crucial to the West's economic and strategic interests. Given the complexity of this new « Eastern question », the Western perspective is important because it counts for a lot in determining the future of this region and in defining the position the Middle East holds in the world System. This dominant perspective has nonetheless the defect of putting on the back burner the interests of the peoples of the Middle East and the possibilities of a different scenario which corresponds less with the designs of the great powers today and more with the needs of the Middle Eastern countries.The present and future position of the Middle East in the world System should thus be examined from an internal viewpoint as much as from an external one. Seen from the outside, the region appears essentially as a pawn. From this perspective, the deterioration of the Palestinian question permits the great powers (particularly the United States) to keep the Arab governments divided and thus blocks the way to regional cooperation susceptible to putting the energy resources of the oil producers at the service of self-directed development in the region. Seen from the inside, however, this cooperation, beyond its economic advantages, has interesting social and cultural possibilities, It is thus a question of knowing which conditions would develop these possibilities. The question is important because, to a certain extent, the outcome of the Middle Eastern situation will serve as an example to the Third World as a whole to the extent that the Middle East develops a strategy for a new kind of development defined and carried out free from dependency on external powers. The precondition to this effort is clearly the formulation and effective maintenance of a common Arab position which is coherent and realistic on the Palestinian question ; inevitably this is central to all Middle Eastern policy.